An atomic force microscopy study of the dissolution of calcite in the presence of phosphate ions - Klasa, J.; Ruiz-Agudo, E.; Wang, L.; Putnis, Christine; Valsami-Jones, E.; Menneken, M.; Putnis, Andrew (2013)
Dissolution of calcite in the presence of phosphate solutions was studied in situ by Atomic Force Microscopy. Results of experiments in slightly alkaline (NH4)2HPO4 solutions showed that dissolution, measured from etch pit spreading, is significantly reduced compared to that observed in pure deionized water, confirming an inhibitory effect of (NH4)2HPO4 on calcite dissolution. However, rates measured in the presence of Na-phosphate solutions at the same pH remained close to that in pure water. This would indicate that the inhibitory effect could be caused by the presence of the View the MathML sourceNH4+ group. Moreover, for phosphate solution concentrations >5 mM, the precipitation of a calcium phosphate phase occurred simultaneously while calcite was dissolving, despite the continuous flow of the reaction solution. Such reactions may play an important role in phosphorus recovery from P-bearing solutions. Importantly this study gives insights into the mechanism of interface-coupled dissolution-precipitation reactions occurring during the interaction of phosphate-bearing solutions with calcium carbonate minerals and emphasizes the importance of performing direct observations when determining the kinetics of dissolution reactions, as they can be significantly affected by the precipitation of secondary phases that could alter dissolution rates determined from measurements of bulk solution composition.